2019 14th Iberian Conference on Information Systems and Technologies (CISTI) 2019
DOI: 10.23919/cisti.2019.8760893
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Artificial Intelligence on Public Administration: A Systematic Literature Review

Abstract: The advent of machines power-driven by Artificial Intelligence (AI) have strongly influenced the world in the 21 st century. The future of AI is promising and is offering a wide range of opportunities for scholars and academics. Although the theme has received a considerable attention over the last years, much has been speculated and little is known about its impacts on the Public Administration. Thus, the purpose of this article is to make the result of those impacts less ambiguous. To this end, we have condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 53 publications
0
23
0
5
Order By: Relevance
“…In addition, the relevance of Scopus is also justified, since it indexes a wide range of AI journals. In that regard, Reis et al [29] found, in March 2019, 127 journals indexed in Scopus that publish research in AI, a surprisingly high number of sources when compared to other databases.…”
Section: Selection Criteriamentioning
confidence: 99%
“…In addition, the relevance of Scopus is also justified, since it indexes a wide range of AI journals. In that regard, Reis et al [29] found, in March 2019, 127 journals indexed in Scopus that publish research in AI, a surprisingly high number of sources when compared to other databases.…”
Section: Selection Criteriamentioning
confidence: 99%
“…Moreover, following the assumptions of Tranfield et al (2003), we used a clear set of steps to be replicated, and only one database to enhance transparency. Scopus was chosen from several relevant databases, such as Web of Science (WoS) or EBSCO Host, because, as justified by Reis et al (2019cReis et al ( , 2020d, has a wider coverage of articles, indexing a broader range of AI journals. With regard to academic search engines, such as Google Scholar, they were excluded because our priority was to select only articles evaluated by peers for reasons of quality and credibility.…”
Section: Methodsmentioning
confidence: 99%
“…This article follows a qualitative analysis of samples retrieved from Scopus.com, which has been used as a bibliographic database of peer-reviewed literature. Selecting this database is justified by Scopus's ability to provide a coverage of articles, as it indexes a broad range of AI journals when compared to other known databases, such as Web of Science from Thomson Reuters [8]. A truly comprehensive approach would lead us to select more than one digital repository, however, given that our priority is transparency and easy reproduction of results, this choice may be acceptable when comparing the pros and cons [29].…”
Section: Methodsmentioning
confidence: 99%
“…Despite the growing interest of academics in the service robots' arena, little academic attention has been devoted to this theme, especially in the hospitality frontline services. Recent developments have been labelled by practitioners, who quite dominate the AI field of knowledge [8]. It is worth noting that AI is a classical domain of Computer Science, with significant contributions since the 1960s.…”
Section: Introductionmentioning
confidence: 99%